Performance and Ancestral Heritage - Gladis Elise Pereira da Silva Kaercher; Gabriel Fortes Pereira (Revista Brasileira de Estudos da Presença, 2022)
Through African and Afro-diasporic references, it is proposed a reflexive exercise on Black children and their performances. Based on studies about Bantu-Kongo cosmology, an approach to Bakongo childhood is sought to provide an understanding of the performances of black Brazilian childhood, relating them to the preservation of African civilizational values. It is concluded, considering ancestral heritage and a cosmological notion of circular time, that Brazilian Black children, through performance, are able to bring together past and present, ancestral and living, renewing memory and keeping the values of Afro-Brazilian civilization alive.